Did Kant suffer from misophonia? - Norena, Arnaud (Frontiers in Psychology, 2024)
Misophonia is a disorder of decreased tolerance to specific sounds, often produced by humans but not always, which can trigger intense emotional reactions (anger, disgust etc.). This relatively prevalent disorder can cause a reduction in the quality of life. The causes of misophonia are still unclear. In this article, we develop a hypothesis suggesting that misophonia can be caused by a failure in the organization of the perceived world. The perceived world is the result of both the structure of human thought and the many conditioning factors that punctuate human life, particularly social conditioning. It is made up of abstract symbols that map the world and help humans to orient himself in a potentially dangerous environment. In this context, the role of social rules acquired throughout life is considerable. Table manners, for example, are a set of deeply regulated and controlled behaviors (it's considered impolite to eat with the mouth open and to make noise while eating), which contribute to shape the way the perceived world is organized. So it's not surprising to find sounds from the mouth (chewing etc.) among the most common misophonic sound triggers. Politeness can be seen as an act of obedience to moral rules or courtesy, which is a prerequisite for peaceful social relations. Beyond this example, we also argue that any sound can become a misophonic trigger as long as it is not integrated into the perceived ordered and harmonious world, because it is considered an "anomaly", i.e. a disorder, an immorality or a vulgarity.